2020
DOI: 10.1101/2020.06.12.147546
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping Connectional Differences between Humans and Macaques in the Nucleus Accumbens Shell-Core Architecture

Abstract: 1Two nucleus accumbens subregions, the shell and core, differ in the patterns whereby 2 they integrate signals from prefrontal and limbic areas of the brain. In this study, we 3 investigated whether the disproportionate volumetric differences of these brain areas, 4 particularly the prefrontal cortex, between humans and macaques are accompanied by 5 unique modifications of their macroscopic integrative connections with the shell and 6 core. More specifically, we characterized the tractographic connectivity pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 84 publications
0
1
0
Order By: Relevance
“…Exploring the modular structure of a community and the connectivity patterns of different functional networks is important for understanding brain mechanisms and evolution. Many neuroscientific studies [59][60][61] have revealed that the brain networks share important organizational principles in common, such as modularity, and that topological modules often comprise anatomically neighboring cortical areas. In addition, the modules of brain networks contain both unilateral and bilateral areas [62], and a community structure in the brain can be correlated with functionally localized regions, such as visual, auditory, and central modules [63].…”
Section: Mapping the Hierarchical Module Structure For Fpc Subregionsmentioning
confidence: 99%
“…Exploring the modular structure of a community and the connectivity patterns of different functional networks is important for understanding brain mechanisms and evolution. Many neuroscientific studies [59][60][61] have revealed that the brain networks share important organizational principles in common, such as modularity, and that topological modules often comprise anatomically neighboring cortical areas. In addition, the modules of brain networks contain both unilateral and bilateral areas [62], and a community structure in the brain can be correlated with functionally localized regions, such as visual, auditory, and central modules [63].…”
Section: Mapping the Hierarchical Module Structure For Fpc Subregionsmentioning
confidence: 99%